2013
DOI: 10.7547/1030480
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Falling Is Prevalent in Older Adults with Diabetes Mellitus But Is Unrelated to Level of Neuropathy

Abstract: Background Patients with diabetic peripheral neuropathy (DPN) demonstrate gait alterations compared with their nonneuropathic counterparts, which may place them at increased risk for falling. However, it is uncertain whether patients with DPN also have a greater fear of falling. Methods A voluntary group of older adults with diabetes was asked to complete a validated fear of falling questionnaire (Falls Efficacy Scale International [FES-I]) and instructed to walk 20 m in their habitual shoes at their habitua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 35 publications
(40 reference statements)
3
37
0
Order By: Relevance
“…Similarly, although in our study diabetes was associated with decreased walking speed, we observed no significant association between diabetes and hand-grip weakness. In addition to loss of lower-limb strength, the following mechanisms have been proposed as potential contributors to the decline in walking speed observed among diabetic individuals: poor sensory and motor peripheral nerve function (46), lower cerebral vasoreactivity (47), poor balance(46) and fear of falls (48).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, although in our study diabetes was associated with decreased walking speed, we observed no significant association between diabetes and hand-grip weakness. In addition to loss of lower-limb strength, the following mechanisms have been proposed as potential contributors to the decline in walking speed observed among diabetic individuals: poor sensory and motor peripheral nerve function (46), lower cerebral vasoreactivity (47), poor balance(46) and fear of falls (48).…”
Section: Discussionmentioning
confidence: 99%
“…[8,11] Additionally, the significant effect of neuropathic pain on FOF and balance was also found in patients with DM by univariate analysis, but peripheral neuropathy was not a factor on balance and FOF. Many studies suggest that peripheral neuropathy significantly influences FOF and balance [8,26,28] On the contrary, Kelly et al [29] and IJzerman et al [6] demonstrated that FOF was prevalent in older adults with DM but it is unrelated to peripheral neuropathy. Lalli et al [30] demonstrated that the presence of neuropathic pain in patients with DM might impair gait and stability resulting in increased falls.…”
Section: Discussionmentioning
confidence: 99%
“…8 Furthermore, DPN has also been found to be one of the independent risk factors for increased risk of falls and fear of falls in older adults with diabetes. [16][17][18][19] Furthermore, fall-related injuries in diabetes are often assumed to trigger a vicious circle as they have potentially detrimental influence on the physical activity levels. This vicious circle of low physical activity, functional deficits and high fall risk further increases health care and economic costs.…”
mentioning
confidence: 99%
“…42 In this scale, scores are treated as continuous variables ranging from 16-64, where 16 indicates no concern and 64 indicates severe concern for falling. Participants in our study were further classified as having low concern (score between [16][17][18][19], moderate concern (score between 20 and 27), or high concern (score ≥28) for falling according to the prior works. 19,43 Balance was measured using two wearable sensors (BalanSens™, BioSensics, Watertown, MA, USA) attached to dominant leg and the lower back.…”
mentioning
confidence: 99%
See 1 more Smart Citation